Micropropagation of Centella asiatica L. An Important Medicinal Herb - Das, R; Hasan, MF; Hossain, MS; Rahman, M (Progressive Agriculture, 2013)
High frequencies of multiple shoot regeneration were achieved from shoot tip explants cultured on MS media fortified with 4.0 mgl-1 BAP + 0.1 mgl-1 NAA. On an average 10.2?0.38 shoots per explant were obtained. The regenerated shoots were rooted in MS medium supplemented with 1.0 mgl-1 IBA. The in vitro grown plantlets were acclimatized and successfully transferred to natural condition with 80% survival. A reproducible protocol was established for in vitro propagation through multiple shoot induction of Centella asiatica L. an important medicinal herb having high medicinal value. DOI: http://dx.doi.org/10.3329/pa.v19i2.16928 Progress. Agric. 19(2): 51 - 56, 2008